Nursing applicants' desire to work in nursing and related factors: a cross-sectional study - Talman, Kirsi (Taylor & Francis, 2025)
Background
The desire to work in the nursing profession has recently been identified as an important aspect to consider in the selection process of nursing students but very little is known about nursing applicants’ or students’ desire to work in nursing.
Aims
The study aimed to describe and explain the desire of undergraduate nursing applicants to work in nursing.
Design
A cross-sectional study design.
Methods
The Desire to Work in Nursing Instrument was used to collect the data. All nursing applicants (N = 974) who took part in an entrance examination organised in six Universities in October 2018 were eligible to participate. Eight Hundred and Forty-one applicants (response rate 86%, 102 males) participated in the study. Statistical analysis included the use of descriptive statistics and linear regression was used to assess if dependent variables explained the observed outcomes.
Results
A strong desire to work in nursing was demonstrated in all the four areas. The most common reason to desire this work was suitability to nursing and the nature of work, and the least common was the career opportunities. Gender, previous education, and a realistic image best explain the desire.
Conclusions
The assessment of desire to work in nursing may assist career choice of nursing applicants, and may enhance recruitment and retention in nursing education. Applicants need to be more aware of the career development possibilities. Further studies are needed to investigate if the desire to work in nursing is different to men than to women to inform recruitment strategies.